The role of Raptor in lymphocytes differentiation and function - Tang, Jianing; Yang, Lu; Guan, Fei; Miller, Heather; Camara, Niels Olsen Saraiva; James, Louisa K.; Benlagha, Kamel; Kubo, Masato; Heegaard, Steffen; Lee, Pamela; Lei, Jiahui; Zeng, Hu; et al. (Frontiers in Immunology, 2023)
Raptor, a key component of mTORC1, is required for recruiting substrates to mTORC1 and contributing to its subcellular localization. Raptor has a highly conserved N-terminus domain and seven WD40 repeats, which interact with mTOR and other mTORC1-related proteins. mTORC1 participates in various cellular events and mediates differentiation and metabolism. Directly or indirectly, many factors mediate the differentiation and function of lymphocytes that is essential for immunity. In this review, we summarize the role of Raptor in lymphocyte function and differentiation, whereby Raptor mediates the secretion of cytokines to induce early lymphocyte metabolism, development, proliferation and migration. Additionally, Raptor regulates the function of lymphocytes by regulating their steady-state maintenance and activation.